Implementación de un portal web para la automatización del proceso de consultorías de mentores gold de la región latinoamericana del ieee (r9), utilizando arquitectura java 2 enterprise edition - j2ee y tecnología ajax - Vera Santana, Diana Cristina (2010)
J2EE is a programming platform for developing and executing applications software with multitier distributed architecture. It is based on a software modular components running over an application server. Ajax is a web development technique used to create interactive applications, running on the client, i.e. in the user’s browser while maintaining communication with the server asynchronously in the background. This paper briefly explains the concepts related to architecture J2EE, Ajax technology and design patterns used in the implementation of a Web portal to automate the consultancies process of mentors in the GOLD Latin American Region of the IEEE There is a description of analysis, design and a test plan used for the modules of Administration, Consulting and Evaluation. Finally, we proposed the conclusions and recommendations defined after the implementation of the project.